Combined effects of EMP and RF field on emotional behavior in mice - Qin, Tongzhou; Liu, Liyuan; Wang, Xing; Guo, Ling; Lin, Jiajin; Du, Junze; Xue, Yizhe; Lai, Panpan; Jing, Yuntao; Ding, Guirong (Frontiers in Public Health, 2023)
Recently, concerns about the combined effects of electromagnetic field (EMF) in daily living and occupational environment are rapidly growing. In this study, we investigated the combined effects of 1-week exposure to electromagnetic pulse (EMP) at 650 kV/m for 1,000 pulses and 4.9 GHz radiofrequency (RF) at 50 W/m2 for 1 h/d in male mice. Open field test, tail suspension test and Y-maze were applied to evaluate anxiety, depression-like behaviors and spatial memory ability, respectively. It was found that compared with Sham group, combined exposure to EMP and RF induced anxiety-like behavior, increased the level of serum S100B and decreased the level of serum 5-HT. The results of quantitative proteomic and KEGG analysis showed that the differentially expressed proteins in hippocampus were enriched in Glutamatergic and GABAergic synapse after combined exposure group, which were verified by western blot. In addition, an obvious histological alteration and autophagy-associated cell death were observed in amygdala instead of hippocampus after combined exposure to EMP and 4.9 GHz RF. These data suggested that combined exposure to EMP and 4.9 GHz RF could induce emotional behavior alteration, which might be associated with Glutamatergic and GABAergic synapse system of hippocampus and autophagy in amygdala.